1999
DOI: 10.1007/s11664-999-0112-0
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of chemical bath deposited CdS thin films

Abstract: CdS thin films have been prepared by chemical bath deposition. As-deposited films are cubic and show a sulfur deficiency. From the transmittance and reflectance data analysis direct band gaps (E g ) ranging from 2.180 to 2.448 eV have been obtained. Air and vacuum annealed samples show a decrease in the band gap. The refractive index (n) lies in the range 1.61-2.34. A dependence of band gap on composition has been observed and the possible reasons are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…The spectral behavior of the optical constants and the band gap value of the CdS thin film, determined by ellipsometric technique in this work, are in good agreement with those of optical constants and band gap values of CdS thin films obtained from reflectance and transmittance measurements in the literature. [2,3,15,23,30] It was shown that the method described here determines successfully the desired optical measurements, and also the optical constants and thickness of thin films simultaneously.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The spectral behavior of the optical constants and the band gap value of the CdS thin film, determined by ellipsometric technique in this work, are in good agreement with those of optical constants and band gap values of CdS thin films obtained from reflectance and transmittance measurements in the literature. [2,3,15,23,30] It was shown that the method described here determines successfully the desired optical measurements, and also the optical constants and thickness of thin films simultaneously.…”
Section: Discussionmentioning
confidence: 91%
“…[13,22,23] Using the diffraction angle and the full width at half maximum (FWHM) of the (111) peak for each the film, the average sizes of the crystallites, L, are determined from the Scherrer formula [24] :…”
Section: Resultsmentioning
confidence: 99%
“…Among various techniques which are used to prepare thin CdS, such as physical vapour deposition (PVD), close-spaced-sublimation (CSS) [4,5], screen printing (SP) [6] and MOCVD [7], chemical bath deposition (CBD) is the most widely used for its low cost and simpleness. Otherwise, it is easy to control the growth rate and can produce reproducible, uniform and adherent films [8][9][10]. In this work, the changes of morphology, structure and optical properties with different pH values and annealing treatments will be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Among various techniques which are used for the preparation of thin CdS, such as physical vapor deposition (PVD), close-spaced-sublimation (CSS) [4,5], screen printing (SP) [6] and MOCVD [7], chemical bath deposition (CBD) is the most widely used for its low cost and simplicity. Also, it is easy to control the growth rate and to produce reproducible, uniform and adherent films [8][9][10]. In this work, the changes of morphology and optical properties with different pH values and annealing treatments are investigated accordingly.…”
Section: Introductionsmentioning
confidence: 99%